Quality of life and its associated factors of Type-2 Diabetes Mellitus patients attending tertiary care hospital, Yavatmal, Central India: A hospital-based cross-sectional study - Rangari, Anchal A; Domple , Vijay K; Kasdekar, Pankaj M; Thakre, Sushama S (Indian Journal of Community Health, 2025)
Background: Type-2 diabetes mellitus (T2DM) is a long-term, incurable disease affecting negatively on quality of life (QoL). Aim & Objectives: To assess the Quality of life of Type-2 Diabetes Mellitus patients attending tertiary care hospital and its associated factors. Methodology: This cross-sectional study was carried out from Dec 2022 to Feb 2023 among 297 T2DM patients attending tertiary care hospital. The data was collected by first author using a 26-item WHOQoL-BREF questionnaire. The Institutional Ethics Committee approved the study. Statistical analysis was done using JASP version 0.18.3 for mean, standard deviation, t-test, ANOVA test, and multiple linear regression (MLR). Results: Mean age of participants was 55.18±11.09 years. Out of total, 57.9% were males, 85.5% of participants were satisfied with their QoL. The mean score of WHOQoL-BREF domains was highest for social relationships (58.78±15.49), while lowest for physical domain (51.83±12.31). The individual perception of overall QoL and health scored 59.59±19.39 and 55.38±18.73 respectively. ANOVA test showed statistical significance between education & socio-economic status with all domains of QoL (P<0.05). MLR reported that socio-economic class II was independently correlated with all domains of QoL. Conclusion: Overall QoL was above average. Education and socioeconomic status of the participants were significantly associated with QoL.